Investigation on Anticataract Activity of Triphala Ghrita - K. N. Mahajan; A. K. Singhai; G. P. Vadnere (E-Journal of Chemistry)
Lab prepared Triphala ghrita was studied for its possible anticataract activity on galactose induced cataract in Swiss albino rats. Administration of Triphala ghrita at a dose of 216 mg/200 g, 1080 mg/200 g and 2160 mg/200 g of rat orally offered significant dose dependent protection against galactose induced cataract and delayed the onset and progression of cataract. It was seen that the dose of 1080 mg of Triphala ghrita did not show stage II cataract in 14 days and stage III in 21 days. It did not show even stage III and stage IV cataract after 30 days whereas group B and group C showed stage III and stage IV cataracts. Dose of 2160 mg did not showed stage IV cataract after 30 days but showed stage III cataract. Dose of 1080 mg of Triphala ghrita offered significant protection against delaying the onset and progression of cataract in comparison to other doses. This effect may be attributed to the antioxidant activity of gallic acid, ellagic acid and ascorbic acid which shows their presence in Triphala ghrita. This preliminary study was encouraging but further studies are required to extrapolate the clinical usefulness of this formulation.